Potential targets of VIVIPAROUS1/ABI3‐LIKE1 (VAL1) repression in developing Arabidopsis thaliana embryos. (21st January 2016) - Schneider, Andrew; Aghamirzaie, Delasa; Elmarakeby, Haitham; Poudel, Arati N.; Koo, Abraham J.; Heath, Lenwood S.; Grene, Ruth; Collakova, Eva
Summary: Developing Arabidopsis seeds accumulate oils and seed storage proteins synthesized by the pathways of primary metabolism. Seed development and metabolism are positively regulated by transcription factors belonging to the LAFL (LEC1, AB13, FUSCA3 and LEC2) regulatory network. The VAL gene family encodes repressors of the seed maturation program in germinating seeds, although they are also expressed during seed maturation. The possible regulatory role of VAL1 in seed development has not been studied to date. Reverse genetics revealed that val1 mutant seeds accumulated elevated levels of proteins compared with the wild type, suggesting that VAL1 functions as a repressor of seed metabolism; however, in the absence of VAL1, the levels of metabolites, ABA, auxin and jasmonate derivatives did not change significantly in developing embryos. Two VAL1 splice variants were identified through RNA sequencing analysis: a full‐length form and a truncated form lacking the plant homeodomain‐like domain associated with epigenetic repression. None of the transcripts encoding the core LAFL network transcription factors were affected in val1 embryos. Instead, activation of VAL1 by FUSCA3 appears to result in the repression of a subset of seed maturation genes downstream of core LAFL regulators, as 39% of transcripts in the FUSCA3 regulon were derepressed in the val1 mutant. The LEC1 and LEC2 regulons also responded, but to a lesser extent. Additional 832 transcripts that were not LAFL targets were derepressed in val1 mutant embryos. These transcripts are candidate targets of VAL1, acting through epigenetic and/or transcriptional repression. Significance Statement: VAL1 suppresses the embryonic program by repressing transcription of core LEC1, AB13, FUSCA3 and LEC2 (LAFL) transcriptional regulators during seed germination. Here we show that VAL1 is also expressed in developing embryos, where it represses a subset of targets of the core LAFL regulators through epigenetic and transcriptional mechanisms, rather than by interfering with their expression.